Iron-Catalyzed One-Pot Four-Component Synthesis of Dihydropyridinones from Benzyl Alcohols and Ketones - Parveen, Humaira; Alsharif, Meshari A.; Alahmdi, Mohammed Issa; Alatawi, Omar M.; Albalawi, Mona O.; Mukhtar, Sayeed; Waheed, Mohd (Synthesis, 2025)
An efficient, facile, and one-pot four-component methodology for the cyclization of readily available benzyl alcohols, acetophenones, Meldrum’s acid, and NH4OAc to access dihydropyridinones (valuable scaffolds in medicinal and synthetic organic chemistry) was established. This four-component cyclization reaction supports the straightforward manufacture of several dihydropyridinones. Several C–C and C–N bonds were constructs to synthesize the desired product. Readily available starting materials, operational simplicity, good to excellent reaction yields, and tolerance of various functional groups are the interesting features of this protocol.
Keywords: Benzyl alcohols; Meldrum’s acid; Dehydrogenation; Knölker catalysts; Dihydropyridinones